Behavioral economics as applied to firms: A primer - Mark Armstrong; Steffen Huck (Center for Economic Studies and ifo Institute (CESifo), 2010)
We discuss the literatures on behavioral economics, bounded rationality and experimental economics as they apply to firm behaviour in markets. Topics discussed include the impact of imitative and satisficing behavior by firms, outcomes when managers care about their position relative to peers, the benefits of employing managers whose objective diverges from profit-maximization (including managers who are overconfident or base pricing decisions on sunk costs), the impact of social preferences on the ability to collude, and the incentive for profit-maximizing firms to mimic irrational behavior.
Keywords: D40; L20; L21; 330; behavioral economics; firms; oligopoly; bounded rationality; collusion; Verhaltensökonomik; Unternehmenspolitik; Beschränkte Rationalität; Test